Nutrition requirement and productivity in clonal minigarden of Toona ciliata var. australis - Freitas de Oliveira, Taiane Pires de (2019)
The nutritional status of the mother plant is essential for the maintenance of vegetative vigor, vital for the production of cuttings. Therefore, the supply of nutrients in optimal amounts during handling of ministumps influences the success of propagation. The objective of this study was to evaluate and compare the productivity of minigarden, nutrients exported by the shoots of three clones of Toona ciliata var. australis and the total consumption of these nutrients during the production period. In each budding collection, the survival was measured, the number of shoots and cuttings produced by the ministump and, the nutritional monitoring was carried out in 18 collections. In the end, the mini-stumps were drawn from gutters to perform a complete nutritional analysis. the consumption curves for 432 days and the total amounts used in the process are presented. The TC3 clone was more productive in the 18 collections of shoots. The TC3 and TC15 clone were more efficient at converting nutrients absorbed to produce sprouts and cuttings. From the 10th collection of cuttings is shown nutritional supplementation to maintain the productivity of the always constant mini-garden. The potassium, nitrogen and calcium are the most exported nutrients by the shoots of the Australian cedar clones.